Counseling and psychotherapy : theories and interventions - Capuzzi, Dave; Gross, Douglas R. (American Counseling Association, 2011)
This student-friendly and well designed introductory text provides a thorough overview of 14 widely used theories. Experts examine each theory from the perspective of its historical background, major constructs, goals, cross-cultural considerations, and limitations. Traditional and brief interventions integrate theory with specific counseling strategies, giving students further insight into the counseling process and guidance in developing their personal counseling style. A consistent case study across chapters reinforces the differences between theories and illustrates assessment of client concerns and treatment planning. Introductory chapters explore core dimensions and brief approaches to the helping relationship, and how to best deliver counseling and advocacy services to diverse client groups. Acomplimentarytest manual and PowerPoints for instructors' use are available by request on university letterhead.